title | author | header-includes | abstract |
---|---|---|---|
Abstract Algebra by Pinter, Chapter 17 |
Amir Taaki |
- \usepackage{mathrsfs}
- \usepackage{mathtools}
- \usepackage{extpfeil}
- \DeclareMathOperator\cis{cis}
- \DeclareMathOperator\ker{ker}
- \DeclareMathOperator\ord{ord}
- \DeclareMathOperator\gcd{gcd}
- \DeclareMathOperator\lcm{lcm}
|
Chapter 17 on Rings |
Prove that the following are commutative rings with unity.
Indicate the zero element, the unity and the negative for an
Ring axioms:
$a \oplus b = b \oplus a$ $(a \otimes b) \otimes c = a \otimes (b \otimes c)$ $a \otimes (b \oplus c) = (a \otimes b) \oplus (a \otimes c)$
Commutative:
$a \otimes b = b \otimes a$
With unity:
$\exists 1' \in A : a \otimes 1' = a$
Axiom 1 is self evident.
Using sage, we prove axioms 2 and 3.
sage: a = var('a')
sage: b = var('b')
sage: c = var('c')
sage: ab = a*b - (a + b) + 2
sage: ab_c = ab*c - (ab + c) + 2
sage: bc = b*c - (b + c) + 2
sage: a_bc = a*bc - (a + bc) + 2
sage: ab_c.full_simplify()
-(a - 1)*b + ((a - 1)*b - a + 1)*c + a
sage: a_bc.full_simplify()
-(a - 1)*b + ((a - 1)*b - a + 1)*c + a
sage: def mul(a, b):
....: return a*b - (a + b) + 2
....:
sage: def add(a, b):
....: return a + b - 1
....:
sage: mul(a, add(b, c)).full_simplify()
(a - 1)*b + (a - 1)*c - 2*a + 3
sage: add(mul(a, b), mul(a, c)).full_simplify()
(a - 1)*b + (a - 1)*c - 2*a + 3
To calculate zero and unity:
Lastly for the negative:
sage: def add(a, b):
....: return a + b + 1
....:
sage: def mul(a, b):
....: return a*b + a + b
Axiom 1:
Self-evident
Axiom 2:
sage: bool(mul(mul(a, b), c) == mul(a, mul(b, c)))
True
Axiom 3:
sage: bool(mul(a, add(b, c)) == add(mul(a, b), mul(a, c)))
True
Commutative:
Self-evident
Zero:
sage: solve(add(a, b) - a, b)
[b == -1]
sage: add(a, -1)
a
Unity:
sage: solve(mul(a, b) - a, b)
[b == 0]
sage: mul(a, 0)
a
Negative
sage: solve(add(a, b) + 1, b)
[b == -a - 2]
sage: add(a, -a -2)
-1
sage: c = var('c')
sage: d = var('d')
sage: e = var('e')
sage: f = var('f')
sage: def add(ab, cd):
....: a, b = ab
....: c, d = cd
....: return (a + c, b + d)
....:
sage: def mul(ab, cd):
....: a, b = ab
....: c, d = cd
....: return (a*c - b*d, a*d + b*c)
....:
Axiom 1:
sage: bool(add((a, b), (c, d)) == add((c, d), (a, b)))
True
Axiom 2:
sage: bool(mul(mul((a, b), (c, d)), (e, f)) == mul((a, b), mul((c, d), (e, f))))
True
Axiom 3:
sage: bool(mul((a, b), add((c, d), (e, f))) == add(mul((a, b), (c, d)), mul((a, b), (e, f))))
True
Commutative:
Self-evident
Zero:
sage: ab_plus_cd = add((a, b), (c, d))
sage: solve(ab_plus_cd[0] - a, c)
[c == 0]
sage: solve(ab_plus_cd[1] - b, d)
[d == 0]
sage: add((a, b), (0, 0))
(a, b)
Unity:
sage: ab_mul_cd = mul((a, b), (c, d))
sage: solve([ab_mul_cd[0] - a, ab_mul_cd[1] - b], c, d)
[[c == 1, d == 0]]
sage: mul((a, b), (1, 0))
(a, b)
Negative
Since
Since normal algebraic operations are defined on A, then 1, 2 and 3 pass. It is also commutative.
Zero: 0
Unity: 1
Negative:
Prove the ring in part 1 is an integral domain.
We show that it has the cancellation property.
Assume
Therefore
Prove the ring in part 2 is a field.
A field is a commutative ring with unity in which every nonzero element is invertible.
Thus
We solve for b as follows
sage: def mul(a, b):
....: return a*b + a + b
....:
sage: solve(mul(a, b), b)
[b == -a/(a + 1)]
(Excluding the
Find the inverse for the ring in part 3.
sage: def mul(ab, cd):
....: a, b = ab
....: c, d = cd
....: return (a*c - b*d, a*d + b*c)
....:
sage: ab_mul_cd = mul((a, b), (c, d))
sage: solve([ab_mul_cd[0] - 1, ab_mul_cd[1]], c, d)
[[c == a/(a^2 + b^2), d == -b/(a^2 + b^2)]]
Let
Ring axioms:
$ab = ba$ $(ab)c = a(bc)$ $a(b + c) = ab + ac$
Commutative:
- ab = ba
Zero:
Unity:
Negative:
Divisors of zero, are any two functions which when
See more here
Any functions which are one to one and have an inverse. That is
A field must have every element invertible. So the ring is not a field.
Ring has divisors of zero, so it does not have the cancellation property
sage: a = var('a')
sage: b = var('b')
sage: c = var('c')
sage: d = var('d')
sage: r = var('r')
sage: s = var('s')
sage: t = var('t')
sage: u = var('u')
sage: w = var('w')
sage: x = var('x')
sage: y = var('y')
sage: z = var('z')
sage:
sage: def add(abcd, rstu):
....: a, b, c, d = abcd
....: r, s, t, u = rstu
....: return (a + r, b + s, c + t, d + u)
....:
sage: def mul(abcd, rstu):
....: a, b, c, d = abcd
....: r, s, t, u = rstu
....: return (a*r + b*t, a*s + b*u, c*r + d*t, c*s + d*u)
Axiom 1:
Self evident.
Axiom 2:
sage: bool(mul((a,b,c,d), mul((r,s,t,u), (w,x,y,z))) == mul(mul((a,b,c,d), (r,s,t,u)), (w,x,y,z
....: )))
True
Axiom 3:
sage: bool(mul((a,b,c,d), add((r,s,t,u), (w,x,y,z))) == add(mul((a,b,c,d), (r,s,t,u)), mul((a,b
....: ,c,d), (w,x,y,z))))
True
sage: bool(mul((a,b,c,d), (r,s,t,u)) == mul((r,s,t,u), (a,b,c,d)))
False
Unity:
sage: solve([x_mul_y[0] - a, x_mul_y[1] - b, x_mul_y[2] - c, x_mul_y[3] - d], r,s,t,u)
[[r == 1, s == 0, t == 0, u == 1]]
Matrices don't have the cancellation property.
For example
Thus is not an integral domain.
Not all matrices are invertible, for example when
Ring axioms:
- \begin{align*} A + B &= (A - B) \cup (B - A) \ &= B + A \end{align*}
$$(AB)C = (A \cap B)\cap C = A \cap (B \cap C) = A(BC)$$ - \begin{align*} A(B+C) &= A\cap [(B - C) \cup (C -B)] \ &= [A \cap (B - C)] \cup [A \cap (C - B) ] \ &= (AB - AC) \cup (AC - AB) \ AB + AC &= (AB - AC) \cup (AC - AB) \end{align*}
Commutativity:
Unity:
Zero:
All elements of
There exist non-zero non-invertible elements in
\begin{align*} e = \varnothing \ a = {a} \ b = {b} \ c = {c} \ ab = {a, b} \ ac = {a, c} \ bc = {b, c} \ abc = {a, b, c} \end{align*}
\begin{tabular}{c | c c c c c c c c c}
\begin{tabular}{c | c c c c c c c c c}
Unity:
sage: a = var('a')
sage: b = var('b')
sage: c = var('c')
sage: d = var('d')
sage: matrix([[a + b*I, c + d*I], [-c + d*I, a - b*I]])
[ a + I*b c + I*d]
[-c + I*d a - I*b]
sage: alpha = matrix([[a + b*I, c + d*I], [-c + d*I, a - b*I]])
sage: matrix([[1, 0], [0, 1]]) * alpha
[ a + I*b c + I*d]
[-c + I*d a - I*b]
Distributive law:
sage: bb = var('e f g h')
sage: cc = var('i j k l')
sage: def make_matrix(xx):
....: return matrix([[xx[0] + I*xx[1], xx[2] + xx[3]*I], [-xx[2] + xx[3]*I, xx[0] - xx[1]*I]])
....:
sage: bool(alpha*(make_matrix(bb) + make_matrix(cc)) == (alpha*make_matrix(bb) + alpha*make_matrix(cc)))
True
Non-commutative:
sage: bool(alpha*make_matrix(bb) == make_matrix(bb)*alpha)
False
\begin{align*}
\alpha &= a \mathbf{1} + b \mathbf{i} + c \mathbf{j} + d \mathbf{k} \
&=
\begin{pmatrix}
a + bi & c + di\
-c + di & a - bi
\end{pmatrix}
\end{align*}
For the formula
sage: ii = matrix([[I, 0], [0, -I]])
sage: ii*ii
[-1 0]
[ 0 -1]
sage: -ii*ii
[1 0]
[0 1]
sage: jj = matrix([[0, 1], [-1, 0]])
sage: jj*jj
[-1 0]
[ 0 -1]
sage: kk = matrix([[0, I], [I, 0]])
sage: kk*kk
[-1 0]
[ 0 -1]
sage: bool(ii**2 == jj**2)
True
sage: bool(ii**2 == kk**2)
True
sage: bool(ii*jj == -jj*ii)
True
sage: bool(ii*jj == kk)
True
sage: bool(jj*kk == -kk*jj)
True
sage: bool(jj*kk == ii)
True
sage: bool(kk*ii == -ii*kk)
True
sage: bool(kk*ii == jj)
True
Show that
sage: alpha
[ a + I*b c + I*d]
[-c + I*d a - I*b]
sage: alpha_bar = matrix([[a - b*I, -c - d*I], [c - d*I, a + b*I]])
sage: bool(alpha_bar*alpha == alpha*alpha_bar)
True
sage: alpha_bar*alpha
[(a + I*b)*(a - I*b) + (c + I*d)*(c - I*d) 0]
[ 0 (a + I*b)*(a - I*b) + (c + I*d)*(c - I*d)]
Note that
Earlier we found the identity is
Thus the multiplicative inverse (both on the left and right) such that
From part 4 we show there is a multiplicative inverse. Thus by the definition,
Let
$f + g = g + f$ $(f \cdot g) \cdot h = f \cdot (g \cdot h)$ $f \cdot (g + h) = f \cdot g + f \cdot h$
For a homomorphism
Applying the rule
\begin{tabular}{c | c c c c c c c c c}
\begin{tabular}{c | c c c c c c c c c}
- \begin{align*} (x_1, y_1) + (x_2, y_2) &= (x_1 + x_2, y_1 + y_2) \ &= (x_2 + x_1, y_2 + y_1) \ &= (x_2, y_2) + (x_1, y_1) \end{align*}
- \begin{align*} (x_1, y_1) \cdot [(x_2, y_2) \cdot (x_3, y_3)] &= (x_1 x_2 x_3, y_1 y_2 y_3) \ &= [(x_1, y_1) \cdot (x_2, y_2)] \cdot (x_3, y_3) \end{align*}
- \begin{align*} (x_1, y_1) \cdot [(x_2, y_2) + (x_3, y_3)] &= (x_1, y_1) \cdot (x_2 + x_3, y_2 + y_3) \ &= (x_1 \cdot (x_2 + x_3), y_1 \cdot (y_2 + y_3)) \ &= (x_1 x_2 + x_1 x_3, y_1 y_2 + y_1 y_3) \ &= (x_1, y_1) \cdot (x_2, y_2) + (x_1, y_1) \cdot (x_3, y_3) \end{align*}
\begin{align*} (x_1, y_1) \cdot (x_2, y_2) &= (x_1 x_2, y_1 y_2) \ &= (x_2 x_1, y_2 y_1) \ &= (x_2, y_2) \cdot (x_1, y_1) \end{align*}
\begin{align*} (1, 1) \cdot (x_1, y_1) &= (1x, 1y) \ &= (x, y) \end{align*}
Divisors of 0 are
Because
In any ring, $a(b - c) = ab - ac$ and $(b - c)a = ba - ca$.
\begin{align*} a(b - c) &= a(b + (-c)) \ &= ab + a(-c) \ &= ab - ac \end{align*}
In any ring, if $ab = -ba$, then $(a + b)^2 = (a - b)^2 = a^2 + b^2.
\begin{align*} (a + b)^2 &= (a + b)a + (a + b)b \ &= a^2 + ba + ab + b^2 \ &= a^2 + ba + (-ba) + b^2 \ &= a^2 + b^2 \end{align*}
\begin{align*} (a - b)^2 &= (a - b)a - (a - b)b \ &= a^2 - ba - ab - (-b^2) \end{align*}
Now to solve this we prove that
$a0 = 0 = 0a$ $x + (-x) = 0$ $a(x + y) = ax + ay$
\begin{align*} (-x)(-y) &= (-x)(-y) + x(-y + y) \ &= (-x)(-y) + x(-y) + xy \ &= (-x + x)(-y) + xy \ &= 0 + xy \ &= xy \end{align*}
\begin{align*} (a - b)^2 &= a^2 - ba - ab - (-b^2) \ &= a^2 - ba - ab + b^2 \ &= a^2 + ab - ab + b^2 \ &= a^2 + b^2 \end{align*}
In any integral domain, if $a^2 = b^2$, then $a = \pm b$.
An integral domain is a commutative ring with unity having the cancellation property.
The cancellation property says:
If
\begin{align*} a^2 - b^2 &= 0 \ &= (a + b)a - (a + b)b \qquad \text{[Note: integral domain is commutative]} \ &= (a + b)(a - b) \end{align*}
Integral domains have no divisors of zero, so
*In any integral domain, only
Note that
Taking the converse, only
Show that the commutative law for addition need not be assumed in defining a ring with unity: it may be proved from the other axioms.
\begin{align*} (a + b)(1 + 1) = (a + b)1 + (a + b)1 &= a(1 + 1) + b(1 + 1) \ a + b + a + b &= a + a + b + b \ (-a) + a + b + a + b &= (-a) + a + a + b + b \ b + a + b &= a + b + b \ b + a + b + (-b) &= a + b + b + (-b) \ b + a &= a + b \end{align*}
Let $A$ be any ring. Prove that if the additive group of $A$ is cyclic, then $A$ is a commutative ring.
Let
Prove if any integral domain if $a^n = 0$ for some integer $n$, then $a = 0$.
But integral domains have no zero divisors. Thus
Prove parts 1-5 are true in a nontrivial ring with unity.
If $a$ is invertible and $ab = ac$ then $b = c$.
Pre-multiply by
An element $a$ can have no more than one multiplicative inverse.
This would imply
If $a^2 = 0$ then $a + 1$ and $a - 1$ are invertible.
\begin{align*} a^2 &= 0 \ a^2 - 1 &= -1 \ (a + 1)(a - 1) &= -1 \ -1(a + 1)(a - 1) &= 1 \end{align*}
Thus the inverse
If $a$ and $b$ are invertible, their product $ab$ is invertible.
\begin{align*} ab(ab)^{-1} &= abb^{-1}a^{-1} \ &= aa^{-1} \ &= 1 \end{align*}
The set $S$ of all the invertible elements in a ring is a multiplicative group.
By above, any
By part 5, the set of all the nonzero elements in a field is a multiplicative group. Now use Lagrange's theorem to prove that in a finite field with $m$ elements, $x^{m -1} = 1$ for every $x \neq 0$.
By Lagrange's theorem, the order of any element in the group must divide the group's order. Therefore let
*If
\begin{align*} yaxa &= y(ax)a = 1 \ &= (ya)(xa) &= xa \end{align*}
Thus
Prove that in a commutative ring, if $ab$ is invertible, then $a$ and $b$ are both invertible.
Thus
If $a \neq \pm 1$ and $a^2 = 1$, then $a + 1$ and $a - 1$ are divisors of zero.
If $ab$ is a divisor of zero, then $a$ or $b$ is a divisor of zero.
Likewise for
In a commutative ring with unity, a divisor or zero cannot be invertible.
Proof by contradiction.
Suppose $ab \neq 0$ in a commutative ring. If either $a$ or $b$ is a divisor or zero, so is $ab$.
Same for
Suppose $a$ is neither $0$ nor a divisor or zero. If $ab = ac$ then $b = c$.
Since
Hence
$A \times B$ always has divisors of zero.
A ring
For every $a \in A$, $a = -a$.
\begin{align*} (a + a)^2 &= (a + a) \ &= a(a + a) + a(a + a) = a^2 + a^2 + a^2 + a^2 = a + a + a + a \ a + a + a + a &= a + a \ a + a + a + a + (-a) + (-a) &= a + a + (-a) + (-a) \ a + a &= 0 \ a + a + (-a) &= -a \ a &= -a \end{align*}
\begin{align*} (a + b) &= (a + b)^2 = a^2 + ab + ba + b^2 = a + ab + ba + b \ ab + ba &= 0 \ ab &= ba \end{align*}
Thus for every
Using the fact
\begin{pmatrix} n + 1\ k \end{pmatrix} $$
Expansion for
\begin{pmatrix} n\ k \end{pmatrix} $$
Hence formula is true by induction.
An element
In a ring with unity, prove that if $a$ is nilpotent, then $a + 1$ and $a - 1$ are both invertible.
\begin{align*} 1 - a^n &= (1 - a)(1 + a + a^2 + \cdots + a^{n - 1}) \ &= (1 - a)(-1 \dot -1)(1 + a + a^2 + \cdots + a^{n - 1}) \ &= (a - 1)(a^{n - 1} + \cdots + a^2 + a + 1) \ &= (1 + a)(1 - a + a^2 - a^3 + \cdots \pm a^{n - 1}) \ &= (a + 1)(1 - a + a^2 - a^3 + \cdots \pm a^{n - 1}) \ &= 1 \end{align*}
Because
In a commutative ring, prove that any product $xa$ of a nilpotent element $a$ by any element $x$ is nilpotent.
In a commutative ring, prove the sum of two nilpotent elements is nilpotent.
In a commutative ring, prove that the product of two unipotent elements $a$ and $b$ is unipotent.
From part 3 above.
In a ring with unity, prove that every unipotent element is invertible.
From part 1 we see
But